NILAI EGALITARIANSME DALAM HUKUM KARMAPHALA - Asli, Luh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2018)
All the creation are governed by the The Law of Karmaphala. Every action of His creation will certainly reward / produce reward. If good behavior is done, then good also result obtained. Con- versely, if the bad behavior is done, then the bad also harvested both during their whole life. This law of Karmaphala binds all of its creations, only in other terms mentioned in terms of causation, action-reaction and others. Karmaphala’s law is fair, objective, scientific, egalitarian and sophisti- cated. It is responsible for averything. If it is not responsible for all that human beings do, the virtues will be metabolized, because the essential principles are powerless to bind them. For that the law of Karmaphala not escape from all of God’s creation, only reward to be accepted there is slowly fast. Nevertheless it still has to be accounted for or the reward for his actions harvested as good as bad, big small karma done. Understanding of the concept of Karmaphala makes a better generation, a generation that obeys the principle.